Safety and Effectiveness Outcomes of a Novel Automated Titanium Suture Fastener Device Applied for Heart Valve Surgery in an Ovine Model - Li, Bin; Bai, Shanshan; Yue, Guangxin; Zhu, Jinyan; Zhang, Min; Yang, Baiqing; Luo, Jiafei; Sun, Yang; Zhang, Leisheng; Wang, Xin (Frontiers in Cardiovascular Medicine, 2022)
Objective: This study was designed to evaluate the operability, effectiveness and safety of the automated titanium suture fastener in a preclinical ovine model in comparison to manual tying in a mitral valve annuloplasty ring implantation surgery. Methods: Eighteen adult Small-tailed Han sheep were prepared for the surgery of mitral valve annuloplasty ring implantation through lateral thoracotomy under cardiopulmonary bypass. A total of 12 stitches were performed to secure an annuloplasty ring, with 6 stitches done with the automated fastener and the other 6 by manual tying. The knotting time for the automated fastener or manual tying was recorded respectively. The firmness of knots, mitral valve integrity, biocompatibility, thrombosis, local reactions and other aspects were also compared at follow-up time (Day 30, 60, 90 and 180). Results: Of the 18 sheep, 16 survived till the designated endpoints and were enrolled for further analysis. Compared to the control group, the knotting time was significantly reduced with the automated fastener (P<0.01). All the annuloplasty rings were tightly secured by 6 fastener clips and 6 hand-made knots without any disengagement or displacement. All the mitral valves were intact without any defect, stenosis, prolapse, valve insufficiency or perforation. Endothelialization rates were comparable between groups 180 days after surgery. Thrombus formed at the thread end of suture instead of the surface of the titanium clip. However, all the thrombi were within the acceptable range for antithrombotic property. Thrombosis on thread ends showed no significant difference between groups 180 days after surgery. No significant differences in inflammatory response and other tissue responses were observed 180 days after surgery. One case of diffuse renal infarction (area ratio =20%) and 1 case of small focal renal infarction (area ratio <5%) were caused by thromboembolism. Conclusions: The automated fastener significantly shortened the time for tying knots for the implantation of the annuloplasty ring in the ovine model, with comparable safety and effectiveness as manual tying.